Flavor and joy: revaluing the collective patrimonial memory of Surquillo Market no. 1 - Revolledo Velarde, René William (2024)
To revalue a historic commercial building is to give it continuous life and if it refers to the flavors and moments of joy of the users, the heritage and its memory are preserved. The objective of this research was to identify the heritage values that generate identity and collective memory in Market No. 1 of the district of Surquillo, in Lima, Peru. Methodologically, this study has a descriptive and interpretative level, used the method of analysis, documentation and hermeneutics and used techniques such as semi-structured interviews, observation and documentary analysis. The main result was that, in the category of patrimonial value of use, economic value predominates since it represents a primary source of subsistence and development, followed in importance by social and sentimental values. It is concluded that these identified heritage values imply a relationship of familiarity with the users that enables the conservation of the property, as it is a "second home" for several generations.